Soil Chemical Properties and Nutrient Status on Various Land Slopes of Gayo Arabica Coffee Plantation, Aceh, Indonesia - Muyassir*, Muyassir; Helmi, Helmi; Rahyunnisa, Meidilla (Aceh International Journal of Science and Technology, 2023)
The chemical and soil nutrients on different land slopes are intriguing and crucial to investigate since they constitute the most significant impediment in sustaining soil fertility in coffee plantations. The issue is whether the slope of the soil can impact the soil's nutrient and chemical characteristics. This study aimed to identify soil chemical characteristics and available nutrients on different slopes of Gayo Arabica coffee plantations. The study used a survey method on smallholder coffee plantations in 6 villages in Bandar District, Bener Meriah Regency, and 12 composite soil samples were taken for laboratory analysis. The determination of the research location and sample points was selected by purposive sampling, with the slope of the land serving as the independent variable and the chemical composition of the soil serving as the dependent variable. The results showed that C-organic, C/N ratio, and base saturation differed significantly at various land slopes, while pH, CEC, N, P, and K were not significantly different. The soil C/N ratio in Gayo coffee plantations is modest, and the amount of C-organic material decreases with increasing land slope. Soil base saturation in Gayo Coffee plantations is very low, where the highest values are found on land slopes of 8-15%. Nitrogen and potassium content are moderate, while Phosphate is very low. The amount of these three nutrients is not affected by the land slope.